Regulatory variants of FOXG1 in the context of its topological domain organisation. (February 2018) - Mehrjouy, Mana; Fonseca, Ana; Ehmke, Nadja; Paskulin, Giorgio; Novelli, Antonio; Benedicenti, Francesco; Mencarelli, Maria; Renieri, Alessandra; Busa, Tiffany; Missirian, Chantal; Hansen, Claus; Abe, Kikue; et al.
Abstract FOXG1 syndrome is caused byFOXG1 intragenic point mutations, or by long-range position effects (LRPE) of intergenic structural variants. However, the size of theFOXG1 regulatory landscape is uncertain, because the associated topologically associating domain (TAD) in fibroblasts is split into two domains in embryonic stem cells (hESC). Indeed, it has been suggested that the pathogenetic mechanism of deletions that remove the stem-cell-specific TAD boundary may be enhancer adoption due to ectopic activity of enhancer(s) located in the distal hESC-TAD. Herein we map three de novo translocation breakpoints to the proximal regulatory domain ofFOXG1 . The classical FOXG1 syndrome in these and in other translocation patients, and in a patient with an intergenic deletion that removes the hESC-specific TAD boundary, do not support the hypothesised enhancer adoption as a main contributor to the FOXG1 syndrome. Also, virtual 4 C and HiC-interaction data suggest that the hESC-specific TAD boundary may not be critical forFOXG1 regulation in a majority of human cells and tissues, including brain tissues and a neuronal progenitor cell line. Our data support the importance of a critical regulatory region (SRO) proximal to the hESC-specific TAD boundary. We further narrow this critical region by a deletion distal to the hESC-specific boundary, associated with a milder clinical phenotype. The distance fromFOXG1 to the SRO ( > 500 kb) highlight a limitation of ENCODE DNase hypersensitivity data for functional prediction of LRPE. Moreover, the SRO has little overlap with a cluster of frequently associating regions (FIREs) located in the proximal hESC-TAD.